2001
DOI: 10.1002/biof.5520140107
|View full text |Cite
|
Sign up to set email alerts
|

Stability of gastrointestinal glutathione peroxidase mRNA in selenium deficiency depends on its 3′UTR

Abstract: Selenoproteins decrease upon selenium-deprivation according to their hierarchical ranking. Whereas classical glutathione peroxidase (cGPx) responds to decreased selenium supply with a complete loss of protein and a marked reduction of mRNA levels, gastrointestinal glutathione peroxidase (GI-GPx) remains detectable and its mRNA is stable. The impact of the 3'UTR on cGPx and GI-GPx mRNA stability was studied in stably transfected HepG2 cells with combinations of mutually exchanged coding regions and 3'UTRs of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…On the other hand, stable selenoproteins are resynthesized faster upon selenium-resupplementation than unstable ones. A destabilization of GI-GPx mRNA was also observed when it was fused to cGPx 3'UTR (Wingler et al, 2001). Also in the family of glutathione peroxidases (GPx) a hierarchy has been observed which can be described as follows: GI-GPx ≥ PHGPx > cGPx = pGPx (Brigelius-Flohé, 1999).…”
supporting
confidence: 85%
“…On the other hand, stable selenoproteins are resynthesized faster upon selenium-resupplementation than unstable ones. A destabilization of GI-GPx mRNA was also observed when it was fused to cGPx 3'UTR (Wingler et al, 2001). Also in the family of glutathione peroxidases (GPx) a hierarchy has been observed which can be described as follows: GI-GPx ≥ PHGPx > cGPx = pGPx (Brigelius-Flohé, 1999).…”
supporting
confidence: 85%
“…Several studies have found that the stability of GPx1 mRNA is enhanced by selenium repletion (11,31,32); however, not all selenoprotein mRNAs are affected by selenium levels (32,33). Transcript stability is often mediated by sequences such as "AU-rich" elements in the 3Ј-UTR of the mRNA (34).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of certain selenoproteins such as Sel P and DIO1 are more resistant to Se deficiency compared to others like GPx1, and regulation of these levels is mainly at the level of mRNA (Hill et al, 1992). There are differences even within the GPx subfamily (GPx1 through GPx4): Se deficiency leads to degradation of GPx1 and GPx3 mRNA before GPx2 and GPx4 mRNA (Weiss Sachdev and Sunde, 2001;Wingler et al, 2001;Muller et al, 2003). Under low Se conditions, the selenoprotein mRNAs are degraded through a process termed non-sense mediated decay (Maquat, 2001;Weiss Sachdev and Sunde, 2001), but transcriptional regulation or protein turnover must also be considered as points of regulation of selenoprotein levels.…”
Section: The Effect Of Decreased Selenium (Se) Intake On Selenoproteimentioning
confidence: 96%